2022
DOI: 10.3390/ijms23094501
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Inflammation in Retinal Disorders: Briefly the State

Abstract: The most frequent retinal diseases, such as diabetic retinopathy, age-related macular degeneration and posterior uveitis, are underlined by oxidative stress or aging-induced retinal inflammation, which contributes to vision impairing or loss. Resolution of inflammation is emerging as a critical phase able to counteract the inflammatory process leading to the progression of retinal damage. Particularly, pro-resolving mediators (PMs) play a key role in the modulation of inflammatory exudates and could be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…In the context of DR, hyperreflective retinal spots (HRS) are clinically observed by physicians using optical coherence tomography. Studies have reported a positive correlation between IBA1-positive MG activation and retinal HRS in patients with non-PDR (NPDR) and PDR [53]. Our results revealed that in the diabetic coculture conditions, G10 and G25, a considerably higher IBA1…”
Section: Impact Of Glucose Levels On Ec and Mg Phenotypessupporting
confidence: 53%
“…In the context of DR, hyperreflective retinal spots (HRS) are clinically observed by physicians using optical coherence tomography. Studies have reported a positive correlation between IBA1-positive MG activation and retinal HRS in patients with non-PDR (NPDR) and PDR [53]. Our results revealed that in the diabetic coculture conditions, G10 and G25, a considerably higher IBA1…”
Section: Impact Of Glucose Levels On Ec and Mg Phenotypessupporting
confidence: 53%
“…It has been described that the increase in the IL-4 release by glial cells may be a mechanism to suppress the exaggerated pro-inflammatory response [ 68 , 69 ], namely the elevated levels of IL-6 and TNF [ 70 ], which seems to be in accordance with our results. Moreover, a pro-inflammatory environment plays an important role in retinal dysfunction [ 71 ], which is in accordance with the alterations in retinal function detected in the untreated ADHD animal model. Moreover, treatment with MPH decreased TNF and iNOS levels and showed a tendency for the same effect concerning IL-6.…”
Section: Discussionmentioning
confidence: 57%
“…Another potentially useful class of such molecules is the lipidic pro-resolving mediators called lipoxins, specifically lipoxin-A4 (LXA4). LXA4 is synthesized in the inner retina and its levels decrease following eye injury ( 73 ). Both NPDR and PDR patients have lower serum levels of LXA4 compared to diabetics without retinopathy; lipoxin-A4 levels were also lower in the vitreous of PDR patients ( 74 ).…”
Section: Role Of Nets In the Complications Of Diabetesmentioning
confidence: 99%